Harnessing chitosan and poly-(γ-glutamic acid)-based biomaterials towards cancer immunotherapy - Beatriz V. Lima; Maria J. Oliveira; Mário A. Barbosa; Raquel M. Gonçalves; Flávia Castro (Materials Today Advances, 2022)
Cancer-related immunosuppression is one of the most challenging aspects of cancer therapy, being one of the principal causes of disease relapse. Most recent immunotherapeutic strategies have been at the forefront of therapies to overcome this problem through targeting T cell-related pathways. Notwithstanding their remarkable clinical success, current immunotherapies have still benefited a small percentage of patients. As such, considering solid tumors are virtually infiltrated by a high proportion of innate immune cells, frequently mentioned as masters of immunosuppression, targeting these cells may offer a durable immune response. Thus, finding new strategies to reprogram the function of innate immune system in the tumor microenvironment is still an unmet clinical need.Biomaterials-based immunomodulatory therapies have been increasingly explored to achieve better cancer treatments. In particular, chitosan (Ch), a polysaccharide derived from the deacetylation of chitin, as well as poly-γ-glutamic acid (γ-PGA), a polymer bacterially synthetized, that can spontaneously self-assemble by electrostatic interactions in different structures, have been preclinically explored for their immunomodulatory properties. Ch and γ-PGA have been found to activate Toll-like receptors, and trigger common pro-inflammatory immune pathways, such as Nuclear factor kappa B (NF-кB) and Mitogen-activated protein kinase (MAPK). Other pathways and receptors, such as the Retinoic Acid Orphan Receptor γt (RORγt), phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT), or the inflammasome have also been shown to be differentially activated by either polymer. Hence the prospective application of Ch/γ-PGA formulations in cancer therapy, in an effort to synergize their effects to heighten the therapeutic response via innate immunity, could constitute a novel immunotherapeutic strategy. This review highlights how Ch and γ-PGA can efficiently reprogram innate immune cells in tumors, and ultimately initiate activation of T cell immunity against advanced cancers. Moreover, the therapeutic potential of Ch/γ-PGA-based biomaterials as adjuvants of conventional cancer therapies and as diagnostic tools is discussed.